2001
DOI: 10.1111/j.1460-2466.2001.tb02885.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Collegiate Academic Performance Decrements: Early Findings

Abstract: Recent research at colleges and universities has suggested that some college students' academic performance might be impaired by heavier use of the Internet. This study reviews the relevant literature and presents data from a survey of 572 students at a large public university. Heavier recreational Internet use was shown to be correlated highly with impaired academic performance. Loneliness, staying up late, tiredness, and missing class were also intercorrelated with self-reports of Internet-caused impairment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
3
20

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(190 citation statements)
references
References 10 publications
8
159
3
20
Order By: Relevance
“…Positive effects can be found in the levels of learning and in the results obtained by students (Leung & Lee, 2012;López-Pérez, Pérez-López, Rodríguez-Ariza, & Argente-Linares, 2013;Markovíc & Jovanovíc, 2012;Mohd & Maat, 2013). There are also studies where no incidence of technology has been found on learning outcomes (Wittwer & Senkbeil, 2008) or negative effects when problems of addiction are present that constitute a social problem (Chou, Condron, & Belland, 2005;Kim, LaRose, & Peng, 2009), having as a consequence the decrease of the student's academic performance (Junco & Cotten, 2011;Kubey, Lavin, & Barrows, 2001). The inclusion of technology in education showed different effects on the academic performance of students, similar studies present contradictory results (Torres-Díaz et al, 2016).…”
Section: Technology and Academic Performancementioning
confidence: 91%
“…Positive effects can be found in the levels of learning and in the results obtained by students (Leung & Lee, 2012;López-Pérez, Pérez-López, Rodríguez-Ariza, & Argente-Linares, 2013;Markovíc & Jovanovíc, 2012;Mohd & Maat, 2013). There are also studies where no incidence of technology has been found on learning outcomes (Wittwer & Senkbeil, 2008) or negative effects when problems of addiction are present that constitute a social problem (Chou, Condron, & Belland, 2005;Kim, LaRose, & Peng, 2009), having as a consequence the decrease of the student's academic performance (Junco & Cotten, 2011;Kubey, Lavin, & Barrows, 2001). The inclusion of technology in education showed different effects on the academic performance of students, similar studies present contradictory results (Torres-Díaz et al, 2016).…”
Section: Technology and Academic Performancementioning
confidence: 91%
“…The focus of different studies has been on younger populations, although some have also taken into account adult populations [32,34,36]. This may reflect the view that this is primarily a disorder of children, adolescents and early adulthood.…”
Section: Epidemiologymentioning
confidence: 99%
“…However, the number of problematic or excessive Internet users among college students' has grown remarkably as well (Cheung, Lee & Lee, 2013;Senol-Durak & Durak, 2011;Kirschner, & Karpinski, 2010;Frangos, Frangos, & Sotiropoulos, 2010;Li, Wang, & Wang, 2009;Chen & Peng, 2008;Ceyhan, 2008). According to the related literature (e.g., Li, Zhang, Li, Zhen & Wang, 2010;Kim, LaRose, & Peng, 2009;Chen & Peng, 2008;Kubey, Lavin, Barrows, 2001) excessive or problematic Internet use (PIU) causes problems in individuals' psychological and social lives and create difficulties in their work and school environments. For instance, a study conducted by Chen and Peng (2008) indicated that problematic or heavy Internet users are more likely to be depressed, physically ill, lonely, and introverted compared to light or moderate Internet users.…”
Section: Introductionmentioning
confidence: 99%